Zygmunt Bauman’s Ethical Warnings in the Area of Economics. The Third Millennium’s Perspective - Matera, Rafał (Annales. Etyka w Życiu Gospodarczym, 2014)
Zygmunt Bauman is not only a sociologist and philosopher reputable in the worldof science, he is also a father figure for people interested in the phenomenon ofglobalization. Bauman investigates how current economic and political changesinfluence the lives of particular societies. It was important to underline that alsoeconomists can make use of Bauman’s ideas but with a few reservations That iswhy the following crucial areas were proposed relating to economic aspects: themeaning of consumptionism and wastage; global inequalities; the reasons andconsequences of the global economic crisis, and some heterodox matters such ashappiness, welfare, and well-being, all of which can be helpful in understandingthe multidimensional globalization process.